The analysis of gen Z’s work motivation during Covid-19 pandemic: the mediating effects of job satisfaction, Hanoi, Vietnam - Nguyen Chi Hai; Liswandi Liswandi (President University, 2022)
At the end of 2019, the Covid-19 pandemic has brought negative effects to the workforce, especially Gen Z. In Vietnam, this is a new generation and has not had much experience. Therefore, there have been certain studies around Gen Z and Covid-19. One of the topics studied by the researcher was Gen Z's work motivation during the Covid-19 pandemic. The research was conducted to find out what elements can drive Gen Z's work motivation through Job Satisfaction. Through the description of quantitative research methods and using Smart PLS 3.3.3 for analysis. The number of survey participants is 200 people living in Hanoi. Based on collected data, the factors Salary, Promotion, Work Freedom, Friendly Environment, and Training have an effect on job satisfaction. Last but not least, Satisfaction has had a significant effect on Gen Z's motivation to work in Hanoi during the Covid-19 pandemic.